Analysis of The Implementation of PSAK No. 71 on Impairment Loss Reserves: A Case Study of State-Owned Pharmaceutical Companies Listed on The Indonesia Stock Exchange (BEI) - Maya Sova; Thorman Lumbanraja; Muhammad Iqbal Ismail (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to analyze the implementation of Statement of Indonesia Financial Accounting Standards (PSAK) No. 71 regarding impairment loss reserves in state-owned pharmaceutical companies listed on the Indonesia Stock Exchange (BEI). PSAK No. 71 is a convergence of International Financial Reporting Standard (IFRS) 9 and provides guidelines for financial instruments. The research adopts a descriptive-analytical approach, utilizing data from financial statements and conducting interviews with relevant stakeholders. The qualitative analysis explores the application of PSAK No. 71 and evaluates the impairment loss reserves in these companies. The findings contribute to a better understanding of the implementation of PSAK No. 71 in state-owned pharmaceutical companies and its impact on financial reporting. The research also provides insights for companies, regulators, and supervisory authorities in the pharmaceutical sector regarding the application of PSAK No. 71.